2021
DOI: 10.21203/rs.3.rs-1025389/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determining Mobile Learning Potentialities in Emerging Computing Paradigms: an Exploratory Approach for Performance Optimization

Abstract: Mobile learning (m-learning) adoption has incredibly increased with the implementation of related computing paradigms. The mobile cloud architectures (MCAs) enable m-learning with several benefits and face limitations with m-learning actors’ changing requirements. IoT, edge, mobile edge, fog, AI, and 5G, bring numerous features and increase m-learning efficiency across educational disciplines. This study investigates the state-of-the-art m-learning architectures, determines a unified m-learning MCA, and explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Yusuf and Jamjoom (2022) highlighted the importance of higher education institutions predicting the specializations and professions needed in the future and working towards equipping students with the associated skills. Mohiuddin et al (2023) recommended identifying the skills necessary to deal with industrial and technological advancements, urging further predictive studies, especially in exploring future professions and their associated skills.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Yusuf and Jamjoom (2022) highlighted the importance of higher education institutions predicting the specializations and professions needed in the future and working towards equipping students with the associated skills. Mohiuddin et al (2023) recommended identifying the skills necessary to deal with industrial and technological advancements, urging further predictive studies, especially in exploring future professions and their associated skills.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Understanding the complex role of English in GCC education is important for international students because it reflects the region's commitment to multilingualism and its potential impact on the academic and social experiences of those who choose to research there (Abou-El-Kheir & MacLeod, 2019). Mohiuddin et al (2023) analysed the Saudi Arabian higher education landscape in the framework of the 2023 Vision. It evaluated the progress and achievements of higher education institutions during the first review cycle (2016-2020) in accordance with the Vision's higher education development strategic objectives.…”
Section: Education Reform In the Gulf Cooperation Council (Gcc) Count...mentioning
confidence: 99%
“…This research identified modern curriculum development, industry-based academic learning outcomes, faculty development, and international collaborations as important priorities, among others. These priorities seek to improve professional competence, close the disparity between educational outcomes and market demands, and establish a knowledge-based society (Mohiuddin et al, 2023). Mohiuddin et al (2023) research provided valuable insights into the capabilities and priorities of Saudi higher education institutions and their role in attaining Vision 2030's objectives, which may have implications for international students contemplating higher education opportunities in Saudi Arabia.…”
Section: Education Reform In the Gulf Cooperation Council (Gcc) Count...mentioning
confidence: 99%
See 2 more Smart Citations